Tinjauan Maqasid al- Shariah terhadap Pengelolaan dan Pengembangan Bank Wakaf Mikro Berkah Rizqi Lirboyo Kediri - Rizqi Mubarok; Muhammad Al Faruq (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
This research is motivated because there are gaps and unequal business development and capital needs for micro-scale community businesses, so the presence of this “Bank Wakaf Mikro” can lift the community's economy by providing capital to productive poor people. This study aims to determine the system of waqf in the “Bank Wakaf Mikro Berkah Rizqi Lirboyo”, and is reviewed using Maqasid al-Shariah. This observation is useful for knowing the maslahat at the level of Maqasid al-Shariah which consists of three levels of dharuriyah, hjiyyah and tahsiniyyah with a focus on five maintenance, namely al-din( religion), an-nafs (soul), al-nasb (descent), al-'aql (mind). This research uses a qualitative study, using three types of methods of extracting data is a primary data source of data in the form of interviews, observation and documentation of secondary data sources. Based on the results of research conducted by researchers, the “Bank Wakaf Mikro Berkah Rizqi Lirboyo” has a mismatch between the use of the term in the name